Correlation of Amniotic Fluid Index with Fetomaternal Outcomes - Kanwal, Munazza; Mushtaq, Qurratulain; Mustafa, Nilofer; Naqvi, Sadiqa Batool; Sheikh, Mehma Nafees; Rabea Al Hassan; Rehman, Mounazza (Indus Journal of Bioscience Research, 2025)
Background: Although abnormal amniotic fluid index (AFI) is associated with unfavorable pregnancy outcomes, its prognostic validity for the entire spectrum of AFI is still up for debate. Ultrasound-based AFI evaluation is a rather easy and non-invasive method that can help physicians with risk assessment and prompt decision-making in environments with limited resources. Objective: To determine the correlation between AFI measured in the third trimester and Fetomaternal outcomes in singleton pregnancies. Methods: Prospective cohort of 126 antenatal women (≥36 weeks gestation) recruited at a tertiary center from November 2024 – April 2025. AFI was measured by four quadrant ultrasound and participants stratified into oligohydramnios (≤5 cm), borderline (5.1–8 cm), normal (8.1–24 cm) and polyhydramnios (>24 cm). Primary outcomes were mode of delivery, Apgar <7 at 5 min, NICU admission and birth weight. Secondary outcomes included meconium stained liquor, postpartum hemorrhage (PPH) and maternal hypertensive disorders. Statistical analysis used χ²/Fisher’s exact test, one way ANOVA and multivariable logistic regression (SPSS v29). Results: Mean maternal age was 27.4 ± 4.9 yrs. AFI distribution: oligohydramnios 23 (20.6 %), borderline 30 (23.5 %), normal 65 (50.0 %), polyhydramnios 08 (5.9 %). Caesarean section (CS) rates rose with decreasing AFI (60 % vs 45 % vs 25 % vs 40 %; p < 0.001). NICU admission was highest in oligohydramnios (28.6 %) and polyhydramnios (30 %) groups (p = 0.004). Mean birth weight showed a moderate positive correlation with AFI (r = 0.35, p < 0.001). Low AFI independently predicted CS (AOR 2.9, 95 % CI 1.4–6.2) and NICU admission (aOR 3.5, 95 % CI 1.4–8.5) after adjusting for parity and gestational age. Conclusion: Both low and high extremes of AFI were associated with unfavorable Fetomaternal outcomes, with oligohydramnios conferring the greatest risk. Routine third trimester AFI assessment can aid in risk stratification and timely obstetric interventions.